Influence Mechanism of Energy Efficiency Label on Consumers’ Purchasing Behavior of Energy-Saving Household Appliances - Si-dai, Guo; Cheng-Peng, Lu; Hang, Li; Ning, Zhu (Frontiers in Psychology, 2021)
Mandatory energy efficiency label is an effective way to change consumers’ consumption habits and guide them to buy energy-saving appliances. However, few studies concerned about the impact of energy efficiency label on consumers’ purchasing behavior. Based on the theory of planned behavior (TPB), social cognitive theory and signaling theory, this paper constructs a theoretical model of the effect of the energy label on consumers’ purchasing behavior of energy-saving household appliances. The survey data of 396 household appliance consumers in Mianyang City, China, are collected by the interception method, and the theoretical model is tested by structural equation modeling (SEM). Empirical results of this study indicate that consumers’ cognition and perceived value of energy efficiency label significantly affect label trust. Perceived value has a significant impact on consumers’ purchasing behavior of energy-saving appliances, while label cognition and label trust indirectly influence consumers’ purchasing behavior through the intermediary variable of purchase intention. External environmental factors such as publicity and education as well as subjective norms affect consumers’ actual purchasing behavior through the intermediary effect of purchase intention. This study provides important insights into the policy intervention measures to promote consumers’ purchasing behavior of energy-saving appliances.